How Students Experience Blended Learning? (Malaysian Experience) - Mohammad Attaran; Zamzami Zainuddin (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2018)
Context This research studied student’s perception of using SPeCTRUM (as a platform for blended learning) at a university in Malaysia. Methods A mixed method design was employed to collect data on students’ perception and experience of using SPeCTRUM in learning activities. A questionnaire, individual interviews, focus group discussion, and class observations were used as instruments for collecting the data. Participants were from the faculty of education, university of Malay (Malaysia). Results The results showed that the students had positive attitudes towards SPeCTRUM regarding its flexibility in learning activities outside the class hours, including students’ peer interaction. However, the findings showed that the instructor had limited time to interact with students virtually on the SPeCTRUM outside the class, and their priority is informative quality. Conclusions According to the results, SPeCTRUM has great flexibility, which allows students to have easy access. It provides the opportunity to save time and allows learning at any time and place.